Engineering properties of epoxy resins used as concrete adhesives - Tu, Lin; Kruger, Deon (2023)
Keywords / palabras clave : absortion , adhesives ; bonding ; creep test ; curing ; jopints ( junctions ) ; pullout tests ; shear tests
Keywords: Resinas; Epoxi; Hormigon